2004
DOI: 10.1074/jbc.m307502200
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-like Factor Epiprofin Is Expressed by Epithelium of Developing Teeth, Hair Follicles, and Limb Buds and Promotes Cell Proliferation

Abstract: We identified a cDNA clone for epiprofin, which is preferentially expressed in teeth, by differential hybridization using DNA microarrays from an embryonic day 19.5 mouse molar cDNA library. Sequence analysis revealed that this cDNA encodes a member of the Krü ppellike factor family containing three characteristic C 2 H 2 -type zinc finger motifs. The full-length cDNA was obtained by the 5 Cap capture method. Except for its 5 -terminal sequence, the epiprofin mRNA sequence is almost identical to the predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 32 publications
6
112
0
Order By: Relevance
“…Sp7 is a zinc-finger transcription factor and a member of the SP gene family, which is highly expressed in proliferating epithelial cells of hair follicles, limbs, and teeth (Nakamura et al, 2004), and it has also been reported to be ubiquitously expressed in adult tissues (Scohy et al, 2000). This is in agreement with the more general localization found by mRNA in situ hybridization in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sp7 is a zinc-finger transcription factor and a member of the SP gene family, which is highly expressed in proliferating epithelial cells of hair follicles, limbs, and teeth (Nakamura et al, 2004), and it has also been reported to be ubiquitously expressed in adult tissues (Scohy et al, 2000). This is in agreement with the more general localization found by mRNA in situ hybridization in this study.…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with the more general localization found by mRNA in situ hybridization in this study. During tooth development, Sp7 is expressed in proliferating dental epithelium and differentiated odontoblasts, and it has been proposed that it may function in the regulation of cell growth (Nakamura et al, 2004). Other members of the SP family, such as Sp4 and Sp6, are also known to be involved in tooth development (Supp et al, 1996;Nakamura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…47 Moreover, mice lacking the function of Epiprofi n, a transcription factor highly expressed in the epithelial component of the tooth germ have multiple supernumerary incisor and molar teeth. 48,49 The formation of these supernumeraries appears to take place after initiation during the bud stage of development, with multiple branched invaginations forming at sites within the primary tooth buds. Signifi cantly, these invaginations are associated with upregulated and extended Lef1 expression within the mesenchymal component of these tooth germs.…”
Section: Wnt Signallingmentioning
confidence: 99%
“…Signifi cantly, these invaginations are associated with upregulated and extended Lef1 expression within the mesenchymal component of these tooth germs. 48,49 Lef1 lies directly downstream of β-catenin, which forms the central component of a cell adhesion complex essential for canonical WNT signalling within the cell. Transgenic mice expressing a stabilised form of β-catenin throughout the oral epithelium demonstrate multiple odontomalike supernumerary teeth, with the tooth buds that give rise to these teeth undergoing a process of continuous renewal 50 and being able to regulate numerous mediators of tooth development.…”
Section: Wnt Signallingmentioning
confidence: 99%
“…5). These include transcription factors such as En1 (Loomis et al, 1996), Dlx2, 5 and6 (Bulfone et al, 1993;Robledo et al, 2002;Kraus and Lufkin, 2006), Msx2 (Davidson et al, 1991), and Sp8, Sp9 and Sp6 (Treichel et al, 2003;Bell et al, 2003;Nakamura et al, 2004); components of signaling pathways such as Bmp2, 4 and 7 (Francis et al, 1994;Lyons et al, 1995) Wnt3a/Wnt3 (Kengaku et al, 1998;Barrow et al, 2003), Notch1, Jag2 and Rfng (Radical fringe; Laufer et al, Sidow et al, 1997;Jiang et al, 1998); the transmembrane protein Flrt3 (Smith and Tickle, 2006) and several epithelial markers such as Cd44 (Wheatley et al, 1993), the connexin Cx43 (Laird et al, 1992), and p63 (Mills et al, 1999;Yang et al, 1999). Several of these mentioned genes are specifically expressed in the AER and can also be considered AER markers (Bell et al, 1998) but others, such as En1, Msx2, Bmps, Sp8, Sp9 and Sp6 exhibit ectodermal domains of expression broader than that of Fgf8.…”
Section: B C D Amentioning
confidence: 99%